2014
DOI: 10.1007/s13365-014-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

JC virus nucleotides 376-396 are critical for VP1 capsid protein expression

Abstract: JC Virus (JCV) infection of the brain can cause Progressive Multifocal Leukoencephalopathy, JCV Granule Cell Neuronopathy and JCV Encephalopathy (JCVE). JCVCPN, isolated from the brain of a patient with JCVE, is a naturally occurring strain of JCV with a 143 base pair deletion in the agnogene. Cell culture studies of JCVCPN have shown that the loss of these nucleotides in the agnogene results in impaired expression of VP1 and infectious virion production. To better understand the role of this DNA sequence in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Experiments with chimeric viruses between JCV CPN and JCV Mad-1 indicated that the agnogene deletion, rather than the kidney-type regulatory region, was the cause of this particular phenotype [37]. Further experiments demonstrated that the deletion of nucleotides 376-396 in the agnogene results in decreased levels of virus DNA replication and a lack of expression of the VP1 capsid protein [38]. Although this observation stems from a single case, these data suggest that the agnogene deletion of this particular JCV strain allowed for the virus to infect and propagate into cortical pyramidal neurons.…”
Section: Jcv Encephalopathy (Jcve)mentioning
confidence: 99%
“…Experiments with chimeric viruses between JCV CPN and JCV Mad-1 indicated that the agnogene deletion, rather than the kidney-type regulatory region, was the cause of this particular phenotype [37]. Further experiments demonstrated that the deletion of nucleotides 376-396 in the agnogene results in decreased levels of virus DNA replication and a lack of expression of the VP1 capsid protein [38]. Although this observation stems from a single case, these data suggest that the agnogene deletion of this particular JCV strain allowed for the virus to infect and propagate into cortical pyramidal neurons.…”
Section: Jcv Encephalopathy (Jcve)mentioning
confidence: 99%
“…Further analysis of the agnoprotein coding region by DNA footprinting, followed by band‐shift assays using nuclear extracts from JCV infected cells, demonstrated that certain cis‐acting DNA elements within the agnoprotein coding gene served as binding sites for infection‐induced factors and contributed to the viral replication cycle (Akan et al, ). Moreover, analysis by Ellis and Koralnik () of a specific agnoprotein coding region deletion mutant (Mad‐1 376–396) isolated from a PML patient's brain samples exhibited substantial defects in viral replication, as had been observed by Akan et al () suggesting that specific regions in the agnoprotein coding region contribute to viral replication, perhaps at the DNA level, in a cis‐acting manner. Furthermore, in support of these findings, Myhre et al () reported that several clinical variants of BK virus with specific agnoprotein gene deletions are also severely defective in gene expression and viral DNA replication but can be rescued by agnoprotein gene expression in cis ‐ and trans‐ complementation experiments, suggesting the importance of agnoprotein for the BKV replication cycle as well.…”
Section: Role Of Agnoprotein In Viral Life Cyclementioning
confidence: 70%
“…Despite these impediments, over recent years, progress has been made and several issues related to JCV and PML have been partially progressed. Studies of the JCV life cycle have provided a better understanding on a number of aspects, including viral attachment and entry to the cell (e.g., by highlighting the roles of sialic acid and serotonin receptors), intracellular transport to the cell nucleus and JCV replication . These developments have, in turn, led to the identification of a number of potential therapeutic targets or biomarkers.…”
Section: Current Issues Related To the Management Of Drug‐induced Promentioning
confidence: 99%